The Mechanisms of Medial Pedicle Wall Violation: Insertion Method Is as Important as Correct Cannulation of the Pedicle - (:unkn) unknown (My University, 2014)
A cadaver study aims to determine the mechanisms of medial pedicle wall violation after a correct cannulation of the pedicle. The study presents finding out the effect of insertion angle and insertion force on medial wall violation. We used 100 lumbar pedicles of cadavers. Special wooden blocks were produced to simulate a fixed angle fault after a correct pedicle cannulation. Pedicles were divided into 4 groups: 10-degree free drive (group 10), 15-degree free drive (group 15), 10-degree push drive (group 10P), and 15-degree push drive (group 15P). After insertion of pedicle screws, laminectomies were done and the pedicles were evaluated from the inside. Pedicle complications were more in group 10P than group 10 ( P = 0.009 ). Medial wall fracture ( P = 0.002 ) and canal penetration were more in group 15P than group 15 ( P = 0.001 ). Groups 10P and 15P were similar regarding medial wall fractures but canal penetration was significantly higher in group 15P ( P = 0.001 ). Medial wall breaches can happen after correct cannulation of pedicles. Change in insertion angle is one factor but the most important factor is the use of a pushing force while inserting a screw. The pedicle seems to be extremely tolerant to insertion angulation mistakes up to 10 degrees and tends to lead the screw into the correct path spontaneously.
The Mechanisms of Medial Pedicle Wall Violation